Are Senior High School Students Interested in Learning Vocabulary in ELT Context Using Instagram Platform? - Fajar Senolinngi; Sri Damayanti; Arny Irhany Asmin (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Vocabulary is one important aspect of learning a foreign language. With a limited vocabulary, anyone will also have a limited understanding. Learning vocabulary therefore is perceived important. However, EFL learners often have a limited acces to learn vocabualary. With the growing of technological uses in language teaching, this study aims at unveil the level of students’ interest in learning vocabulary through Instagram. The quantitative approach therefore is used in this study. The study involves 49 senior high school students of SMAN 1 Palopo. The findings indicate that that the average score of students’ interest in learning vocabulary through Instagram is 67,58. The highest percentage of the result is 44.41% that indicates that the students of SMAN 1 Palopo are interested in learning vocabulary through Instagram.